1973
DOI: 10.1038/bjc.1973.38
|View full text |Cite
|
Sign up to set email alerts
|

The Concentration of Free and Conjugated 3-Hydroxyanthranilic Acid in the Urine of Bladder Tumour Patients Before and After Therapy, Measured with an Enzymatic Method

Abstract: Summary.-The basal concentration of the tryptophan metabolite 3-hydroxyanthranilic acid (30HA), which has carcinogenic properties, was measured with an enzymatic method of determination which allowed separate measurement of free and conjugated 30HA. The concentration of free 30HA in untreated bladder cancer patients was significantly (P < 0.001) higher than in a healthy control group, but after local therapy the concentration was significantly lower than before treatment (P < 0-01). The concentration of conjug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
3

Year Published

1975
1975
1990
1990

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
0
3
0
3
Order By: Relevance
“…3-HANA has long been known as an integral link in the kynurenine pathway, the primary route of tryptophan degradation in mammalian cells. Because of its possible role in the pathogenesis of bladder cancer (Boyland and Williams, 1956;Benassi et al, 1963;Teulings et al, 1973), which has been speculatively related to its ability to interfere with mitochondria1 oxidative phosphorylation (Quagliariello et al, 1964), 3-HANA received substantial attention from researchers in the 1950s and 1960s (Gorrod et al, 1967). Studies focussed on the disposition of the substance in urine where 3-HANA occurs in both conjugated and free forms (Brown and Price, 1956;Price et al, 1965), and on the enzymatic mechanisms which are responsible for the hydrolysis of conjugated 3-HANA (Watanabe and Minegishi, 1972;Watanabe et al, 19723).…”
Section: Discussionmentioning
confidence: 99%
“…3-HANA has long been known as an integral link in the kynurenine pathway, the primary route of tryptophan degradation in mammalian cells. Because of its possible role in the pathogenesis of bladder cancer (Boyland and Williams, 1956;Benassi et al, 1963;Teulings et al, 1973), which has been speculatively related to its ability to interfere with mitochondria1 oxidative phosphorylation (Quagliariello et al, 1964), 3-HANA received substantial attention from researchers in the 1950s and 1960s (Gorrod et al, 1967). Studies focussed on the disposition of the substance in urine where 3-HANA occurs in both conjugated and free forms (Brown and Price, 1956;Price et al, 1965), and on the enzymatic mechanisms which are responsible for the hydrolysis of conjugated 3-HANA (Watanabe and Minegishi, 1972;Watanabe et al, 19723).…”
Section: Discussionmentioning
confidence: 99%
“…In previous papers (Teulings et al, 1973(Teulings et al, , 1975 we have demonstrated that the basal urinary concentration of free 3-hydroxyanthranilic acid, which as a mean was found to be high in patients with untreated bladder cancer, is significantly lower in patients treated for the disease. The importance of this observation is that the presence of tumor in the urinary tract might be.…”
mentioning
confidence: 67%
“…It was hypothesized that metabolites of tryptophan, increasingly generated by faulty metabolism, may be the etiological agents in non-industrial bladder cancer. That an abnormal metabolism of tryptophan occurs in certain patients with bladder cancer was concluded from studies in which the functional capacity of the pathway was tested by loading the patients with tryptophan (Brown et al, 1960).In previous papers (Teulings et al, 1973(Teulings et al, , 1975 we have demonstrated that the basal urinary concentration of free 3-hydroxyanthranilic acid, which as a mean was found to be high in patients with untreated bladder cancer, is significantly lower in patients treated for the disease. The importance of this observation is that the presence of tumor in the urinary tract might be.…”
mentioning
confidence: 99%
“…Além disso, HK pode suprimir a proliferação de linfócitos T-CD4 + e induzir o desenvolvimento do fenótipo regulatório (Zaher et al, 2011). AA e HAA estão envolvidos com a etiologia do câncer de bexiga (Teulings et al, 1973) e ambos metabólitos podem auto-oxidar e gerar radicais intermediários mutagênicos que podem interagir com o mesmo receptor da KYN, o AhR (Chung et al, 2011). Além disso, o aumento de HAA induz apoptose em linfócitos T CD8 + , e a proliferação de todos os tipos de linfócitos é bloqueada (Weber et al, 2006).…”
Section: Metabolismo Do Trp No Microambiente Tumoralunclassified
“…A enzima KYNU, responsável pela conversão de KYN em AA e HAA teve um aumento significativo de 30 vezes após 48 horas de radiação com a dose de 3 J/cm² em melanomas. Esses dois metabólitos já foram descritos e relacionados a outros tipos de tumores, como no câncer de bexiga (Teulings et al, 1973) et al, 2009).…”
Section: Ensaio De Viabilidade Celular Por Mtt (Brometo De (3-45-dimunclassified